Health literacy status of pregnant women and women with young children in Tasmania. Issue 1 (4th November 2022) - Melwani, Satish; Cleland, Verity; Patterson, Kira; Nash, Rosie
Abstract: Issue Addressed: The literature provides evidence that maternal health is strongly linked with noncommunicable diseases (NCDs) and their associated risk factors. Enabling women with the asset of health literacy may help to reduce the intergenerational impact of NCDs. However, little is known about the health literacy of pregnant women and women with young children in Tasmania and globally. This study aimed to identify the health literacy status of pregnant women and women with young children (0‐8 years) living in Tasmania and describe their health literacy status according to their demographic characteristics. Methods: An online cross‐sectional survey was undertaken. The survey included demographic questions and a health literacy questionnaire (HLQ). The description of demographic differences across the HLQ scales focused on effect sizes (ES) for standardised differences in mean health literacy scores. The differences found to be statistically significant at P  < 0.05 were also included. Results: 194 participants completed the survey with a mean age of 35.3 years. 73.2% were married, 16.5% were pregnant, 93% had one or more children and 81.5% were university educated. For the first five HLQ scales (score range 1‐4), the lowest overall score was seen for the scale "Actively managing my health" (mean = 2.96; SD = 0.54). For the last four scales (score range 1‐5), the lowest overall score was seen for the scale "Navigating the health care system" (mean = 3.75, SD = 0.67). Nonpregnant women, women with children, women with chronic health conditions and nonmarried women experienced more health literacy challenges. Conclusion: Women in our study showed various strengths and challenges with mean scores varying across the nine HLQ scales. Understanding the health literacy needs of women will enable health services to co‐design solutions and interventions capable of responding to the evolving health needs of pregnant women and women with young children. This approach will ensure that codesigned solutions can engage the end‐user in healthy lifestyle practices and the solutions are sustainable. So What?: We must shift away from a "one size fits all" approach to tailor services to respond to the differing health literacy needs of pregnant women and women with young children to support healthy lifestyle practices and reduce the NCD burden.